Factors governing the affinity and selectivity of histone deacetylase inhibitors for the HDAC8 enzyme active site: Implications for anticancer therapy. (19th July 2021) - Toshev, Nikolay; Cheshmedzhieva, Diana; Dudev, Todor
Abstract: Disruptions in post‐translational modifications of chromatin structure promote uncontrollable cell growth branded as a hallmark of tumor lesions. The overexpression/hyperactivity of histone deacetylases (HDACs) is a common feature for the tumorogenesis and cancer progression. Several inhibitors of histone deacetylases (mainly hydroxamic acid derivatives) have been successfully used as drugs in fighting tumor formations. However, there is no systematic study on the factors controlling the affinity and selectivity of this type of inhibitors to the host enzyme thus hampering successful rational design of more potent and selective anticancer drugs. Herein, in an attempt to unravel the mechanism of the host–guest interactions in these systems at atomic level, we systematically study the effect of various factors in the process and elucidate its key determinants. Density functional theory calculations have been employed. Our findings have the potential to be employed as guidelines in designing new HDAC inhibitors with improved anticancer properties. Abstract : Density functional calculations on complexes between a series of inhibitors and HDAC8 active site have been employed in unraveling the key factors governing the affinity and selectivity of the host enzyme for the guest substances. The findings could serve as guidelines in designing new HDAC8 inhibitors with improved anticancer properties.